Study on the distribution characteristics and metabolic mechanism of chlorine-resistant bacteria in indoor water supply networks. (1st July 2023) - Wang, Mengyuan; Zhang, Ying; Niu, Zhiguang; Miao, Qinkui; Fu, Wei
Abstract: The presence and attachment of chlorine-resistant bacteria on the surface of water distribution network will deteriorate water quality and threaten human health. Chlorination is critical in drinking water treatment to ensure the biosafety of drinking water. However, how disinfectants affect the structures of dominant flora during biofilm development and whether the changes are consistent with the free flora remain unclear. Therefore, we investigated changes in species diversity and relative abundance of different bacterial communities in planktonic and biofilm samples at different chlorine residual concentrations (blank, 0.3 mg/L, 0.8 mg/L, 2.0 mg/L and 4.0 mg/L), and the main reasons for the development of chlorine resistance in bacteria was also discussed. The results showed that the richness of microbial species in the biofilm was higher than that in planktonic microbial samples. In the planktonic samples, Proteobacteria and Actinobacteria were the dominant groups regardless of the chlorine residual concentration. For biofilm samples, the dominant position of Proteobacteria bacteria was gradually replaced by actinobacteria bacteria with the increase of chlorine residual concentration. In addition, at higher chlorine residual concentration, Gram-positive bacteria were more concentrated to form biofilms. There are three main reasons for the generation of chlorine resistance of bacteria: enhanced function of efflux system, activated bacterial self-repair system, and enhanced nutrient uptake capacity. Graphical abstract: Image 1 Highlights: Gram-positive bacteria are mostly present in biofilms under chlorinated conditions. Three metabolic mechanisms were upregulated in microorganisms after chlorination. Only at high chlorine concentrations did the Actinobacteria dominate in the biofilms. Microplankton can remain stable at high chlorine residual concentrations.